Relationship between Islamic human resource practices, supervisory supports and Islamic work ethics (IWE) on employee retention - Nur Yusra Afifah, Nasharudin (2019)
In recent year, the management of human resource (HR) is increasingly widespread among organization in Malaysia. Started in 1980, the influences of Islam on human resource management (HRM) practices in Malaysia with introduce Islamic value in the organization (Junaidah, 2010). This study relationship between Islamic HR practices, supervisory support and Islamic work ethic on employee retention among employees at education department of Kedah (JPNK). In this cross-sectional study, three independent variables in HRM practices namely Islamic HR practices, supervisory support and Islamic work ethic were tested against employee retention. 180 respondents participated in this study from employees in JPNK. The methodology for this research are used questionnaire and quantitative of research design. The results analyzed by using a statistical tool and use the SPSS software version 22. The determination of this research is to know the relationship between Islamic HR practices, supervisory support and Islamic work ethic in according to the Islamic approaches with compliance to al-Quran and al-Sunnah.